Application of Aloevera Compress to Reduce Fever in Children - Alifka Pratiwi; Indrawati Indrawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Fever is one of the common symptoms in children that can be caused by viral or bacterial infections. Treatment of fever generally uses antipyretic drugs, but natural methods such as compresses are often applied as additional therapy. Aloe vera is known to have antipyretic and anti-inflammatory properties that can help lower body temperature naturally. Implementing the intervention of giving Aloe vera compresses to reduce fever in children based on the results of body temperature measurements before and after the intervention in 10 child patients with fever. This study analyzed body temperature changes before and after administering Aloe vera compresses to 10 children with fever. Temperature was measured with a digital thermometer, and the significance of the changes was determined using appropriate statistical methods. The results of the intervention showed that out of 10 patients, 8 children experienced a decrease in body temperature after being given Aloe vera compresses, while 2 children did not show significant changes in temperature. The temperature decrease that occurred ranged from 0.1°C to 0.3°C after the intervention. This shows that Aloe vera compresses can help lower children's body temperature, although its effectiveness may vary depending on the condition of each patient. Aloe vera compress can be a safe non-pharmacological therapy alternative to help reduce fever in children. However, further research is needed with a larger sample size and consideration of other factors that may affect its effectiveness.